Determining the Factors and Evolutionary Trends of Customer Engagement in Businesses: A Bibliometric Analysis - Reza Abbasi Mobarakabadi; Amir khanlari; Nader Seyyedamiri (‫مدیریت بازرگانی)
Objective Over the recent years, the concept of customer engagement has emerged as a focal point in marketing research. Despite the increasing interest in this concept, there is a lack of a comprehensive body of research in this area. Additionally, existing research in this field has focused on small segments rather than taking a holistic view of customer engagement literature. Furthermore, different theoretical perspectives have led to a fragmented theory. In light of this gap, the present study aims to delineate the evolutionary trajectory of customer engagement literature and outline the knowledge structure of the field, providing a comprehensive perspective.